Solomon Islands Education Management Information Systems : SABER Country Report 2015 - World Bank Group (World Bank, Washington, DC, 2016)
In 2011, the World Bank Group commenced a multiyear program designed to support countries in systematically examining and strengthening the performance of their education system. Part of the World Bank’s new Education Section Strategy, this evidence-based initiative, called SABER (Systems Approach for Better Education Results), is building a toolkit of diagnostics for examining education system and their component policy domains against global standards and best practices of countries around the world. The objectives of this report are to examine the system according to key policy areas, identify successes and challenges in the system, and provide recommendations to support the advancement of EMIS in Solomon Islands. Recommendations and activities aim to improve overall EMIS functionality in a sustainable and effective manner to ensure better access and use of information for decision making, planning, and student learning. This profile summarizes key points are as follows: Institutionalization of EMIS as the core management information system of the government will require strong policies and a dedicated EMIS budget. The policy should include clearly outlined mandatory practices to be adopted by various education stakeholders at each level of the education system. Efforts should be made to improve the local capacity of EMIS staff by investing in their professional development activities. EAs should be involved in the process of data collection, processing, and dissemination. The type of data collected and indicators produced by EMIS must be reviewed and further developed to include student level data. Integration of other education databases into EMIS will result in more effective utilization of education data for decision making. EMIS needs to be supported by regular internal and external audits to improve the accuracy of data collected and utilized indecision making. The quality of feedback reports sent to schools should be enriched with more relevant micro level information on school performance. Clearly articulated data utilization and dissemination strategies need to be developed, including processes to ensure the timely production of an annual statistics handbook, as well as additional utilization and dissemination opportunities such as pamphlets and web-based portals.